Genetic diversity and characterization of mungbean germplasm through morphological characters and microsatellite markers / Fatemeh Abna - Abna, Fatemeh (2013)

(untitled)
Twenty mungbean accessions were characterized and their genetic diversity was studied. Eight morphological characters including, plant height, number of fruiting branches per plant, number of pod per plant, number of pod clusters per plant, pod length, number of grains per pod, 1000 grain weight and total grain yield per plant were measured. Analysis of variance for all traits showed significant differences among genotypes. For cluster analysis UPGMA method was used to determine genetic variation and four main groups were defined. Principal component analysis was done to evaluate diversity, three components explained near 79% of total variation among genotypes. The first principal component (PC1) is related to number of Fruiting Branches/Plant, number of pod /plant, number pod cluster and pod length that, explained 39.4% of total variability. Phenotypic coefficients of variation (PCV) and genotypic coefficients of variation (GCV) were calculated for all characteristics, the highest GCV and PCV were observed for number of pod per plant (39.47%, 38.65%), number of pod cluster (34.28%, 32.15%) and grain yield (31.73%,30.90%) respectively. Higher broad sense heritability was found for the same traits. The results of phenotypic and genotypic correlation analysis indicated that grain yield was positively and significantly associated with pod length and 1000 grain weight. Path analysis based on genotypic correlation coefficients showed high positive direct effect of number of pod per plant (1.874), number of fruits (0.985) and plant height (0.688) on yield per plant. Furthermore, Twenty two microsatellite primer pairs were used for molecular studies. Out of these, thirteen primers were able to amplify the mungbean genome, upon polymerase chain reaction (PCR) result. Those that failed either were unable to amplify product at all, or showed unspecific amplification. Out of these 13 iii successfully amplified loci, 6 potential polymorphic loci were observed from microsatellite banding profiles on the gel images. These six primer pairs were used to evaluate the genetic variability in six selected mungbean population. The highest expected heterozygosity value count during multi population analysis demonstrated by locus LR7322B, ranged from 0.6014 to 0.8743, whilst the highest observed heterozygosity ranged from 0.5000 to 1 and 0.6666 to1 demonstrated by locus LR7323A and LR7319B respectively. Polymorphism assessments on all populations achieved using these three primers showed that HO scored were generally higher than HE. There was no linkage disequilibrium (LD) observed between all primer pairs. All loci, except LR7319B conformed to Hardy-Weinberg equilibrium (HWE). The FIS index demonstrated no indication of inbreeding among individuals of each population. Corresponding to UPGMA tree, population NM-1919 and population 40521 were observed to be least similar compared to the other four populations. Population structure analysis of molecular marker data from 6 primer pairs also divided the populations into four distinct groups and corresponding to this analysis, 40521 was observed to be least similar compared to the other populations. Furthermore, result obtained from analysis of molecular variation (AMOVA) showed significant difference within individuals of high and low yield mungbean genotypes, and accordingly, high heterosis effect may be accrued in the previous population.